The throne vs. the kingdom: Founder control and value creation in startups - Wasserman, Noam (Strategic Management Journal, 2017)
Research summary: Does the degree to which founders keep control of their startups affect company value? I argue that founders face a “control dilemma” in which a startup's resource dependence drives a wedge between the startup's value and the founder's ability to retain control of decision making. I develop hypotheses about this tradeoff and test the hypotheses on a unique dataset of 6,130 American startups. I find that startups in which the founder is still in control of the board of directors and/or the CEO position are significantly less valuable than those in which the founder has given up control. On average, each additional level of founder control (i.e., controlling the board and/or the CEO position) reduces the pre‐money valuation of the startup by 17.1–22.0 percent . Managerial summary: A founder's vision and capabilities are key ingredients in the early success of a startup. During those early days, it is natural for the founder to have a powerful, central role. However, as the startup grows, founders who keep too much control of the startup and its most important decisions can harm the value of the startup. Both qualitative case studies and quantitative analyses of more than 6,000 private companies highlight that startups in which the founder has maintained control (by retaining a majority of the board of directors and/or by remaining as CEO ) have significantly lower valuations than those where the founder has relinquished control. This is especially true when the startup is three years old or more . Copyright © 2015 John Wiley & Sons, Ltd.